Stachys pilifera Benth: A Review of Its Botany, Phytochemistry, Therapeutic Potential, and Toxicology. (8th June 2022) - Sadeghi, Heibatollah; Rostamzadeh, Davoud; Panahi Kokhdan, Esmaeel; Asfaram, Arash; Doustimotlagh, Amir Hossein; Hamidi, Neda; Hossein, Sadeghi
Abstract : Background . Stachys L. (Lamiaceae) includes more than 300 annual or perennial species growing in temperate regions of Southern Africa, the Mediterranean, America, and Asia. Stachys pilifera Benth ( S. pilifera ), also known as Marzeh Kuhi, is an endemic species from Iran. It is found in the mountainous habitats of the Zagros area. It has various traditional uses, and the phytochemical ingredients and some biological activities of this species have been examined in previous studies. Methods . PubMed, Science Direct, Google Scholar, Scopus, and Science Web databases were used to gather the data. The purpose of this review is to consolidate the scattered knowledge reported in the literature about botany, traditional uses, phytochemistry, pharmacological properties, and safety of S. pilifera and suggest its potential medicinal properties. Key Findings . In traditional Iranian medicine, S. pilifera manages various illnesses, such as rheumatoid arthritis, common cold, infections, asthma, and tussive. More than 30 compounds have been identified in S. pilifera essential oil. The compounds found in S. pilifera are phenolic compounds, monoterpenes, sesquiterpenes, flavonoids, alkaloids, and terpenoids, which have various properties such as antioxidant, nephroprotective, anti-inflammatory, antimicrobial, hepatoprotective, and anticancer properties. Conclusions . The literature reveals that S. pilifera is an essential source of bioactive phytochemicals and illustrates the unknown area of this plant for new investigations. Moreover, we recommend that future research focus on toxicology and quality control studies for S. pilifera to fill the knowledge gap and provide theoretical support for the plant's possible functional and clinical uses.